Loss of heat acclimation capacity could leave subterranean specialists highly sensitive to climate change. (16th October 2020) - Pallarés, S.; Colado, R.; Botella‐Cruz, M.; Montes, A.; Balart‐García, P.; Bilton, D. T.; Millán, A.; Ribera, I.; Sánchez‐Fernández, D.
Abstract: Physiological traits are key in determining the vulnerability of narrow range, highly specialized animals to climate change. It is generally predicted that species from more stable environments possess lower thermal tolerance breadths and thermal plasticity than those from more variable habitats – the so‐called 'climatic variability hypothesis'. However, evolutionary trade‐offs between thermal breadth and its plasticity are also seen in some taxa, and the evolution of thermal physiology remains poorly understood. Subterranean environments are excellent systems for exploring these issues, being characterized by stable climatic conditions, with environmental variability increasing predictably from deep to shallow habitats. Acclimation capacity will be fundamental in determining the sensitivity of subterranean species to climate change, since they have poor dispersal capacity and limited possibility to exploit thermally different microhabitats in the uniform cave environment. We assessed critical thermal maximum (CTmax ) and short‐term heat acclimation capacity in three related beetles (Leiodidae: Leptodirini) with differing degrees of specialization to the subterranean environment (deep, shallow and facultatively subterranean, respectively) and therefore exposed to contrasting thermal variability in nature. Only the facultative subterranean species showed any acclimatory capacity, also having the highest CTmax across the taxa studied. However, this species might experience the highest thermal stress in its habitat under climate change. The studied subterranean specialists will be poorly able to cope physiologically with temperature increase, but in contrast exposed to lower magnitude and rate of warming. Our results fit the climatic variability hypothesis, suggesting that adaptation to cave conditions has selected against the retention of acclimation mechanisms. We show that the pathways that determine vulnerability of subterranean species to climate change depend on their degree of specialization to deep subterranean environments. This information, combined with evaluation of exposure to climatic changes at their present locations, is fundamental in identifying species or populations at greatest risk. Abstract : Acclimation capacity will be fundamental in determining the sensitivity of subterranean species to climate change, since they have poor dispersal capacity and limited possibility for behavioural thermoregulation in the uniform cave environment. We assessed critical thermal maximum (CTmax ) and heat acclimation capacity in three related beetles (Leiodidae: Leptodirini) with differing degrees of specialization to the subterranean environment (deep, shallow and facultatively subterranean) and therefore exposed to contrasting thermal variability in nature. Our results fit the climatic variability hypothesis, suggesting that adaptation to cave conditions has selected against the retention of acclimation mechanisms. We show that the pathways that determine vulnerability of subterranean species to climate change depend on their degree of specialization to deep subterranean environments.